Cell & Bioscience - Shi, Yun-Bo
Cell & Bioscience, the official journal of the Society of Chinese Bioscientists in America, is an open access, peer-reviewed journal that encompasses all areas of life science research. The average time from submission to a first decision is 28 days. Topics of interest include, but are not limited to:  Aquaculture/Aqua Biotechnology  Biodiversity/Evolution Biology  Bio-entrepreneurship  Cancer Biology  Chemical Biology  Chromosome Biology/Gene Regulation  Developmental biology  Drug discovery/Therapeutics  Emerging Biotechnologies  Enzymology/Biochemistry  Genetics/Epigenetics/Genomics  Immunology/Pathogen Biology/Infectious Diseases  Metabolic diseases  Microbials/Biofuels  Molecular and cellular biology  Neurosciences/Neurological Diseases  Pharmacology/Chinese Traditional Medicine  Plant Biology  Post-translational Modifications/Proteomics  Stem Cell Biology  Structural Biology  Tropical Diseases Cell & Bioscience aims to promote research in biosciences and advance biological and medical knowledge in all fields.